Pemodelan Graf Pengetahuan di Kesehatan: Sebuah Analisis Bibliometrik - Muhammad Furqon; Nina Najwa; Deny Hermansyah; Mohammad Zarkasi (Politeknik Caltex Riau, 2022)
Healthcare issues are currently the most researched issues worldwide. Many healthcare researchers collaborate with non-healthcare researchers to improve the quality of healthcare. The knowledge graph is a widely used computer science and mathematics approach to solve healthcare issues. It can model the relationship between events to build new knowledge. Hence, a comprehensive study on knowledge graph modeling in healthcare was conducted in this study. The research methodologies in this study were: (1) article retrieval and general bibliometric analysis; (2) visualization of research distribution; and (3) research recommendations. In the last three years, 867 articles were retrieved from three databases. The citation metrics analysis was also conducted to determine the quality level of articles retrieval. An analysis was conducted using network and density visualization related to the relationship between research topics and trends. The final results in this paper are recommendations for research topics and research titles related to knowledge graph modeling in healthcare.